One Health and Agri-Food Systems - McDermott, John (2021)
John McDermott POLICY SEMINAR CGIAR COVID-19 Hub Seminar: COVID-19 and Implications for One Health Research Co-Organized by CGIAR COVID-19 Hub and IFPRI MAY 4, 2021 - 09:30 AM TO 11:00 AM EDT